OPTIMALISASI PENERIMAAN PAJAK DAN RETRIBUSI DAERAH DALAM RANGKA PENINGKATAN PENDAPATAN ASLI DAERAH KABUPATEN SIDENRENG RAPPANG - Fatimah, Sitti; Ahmad, Jamaluddin; Nur, Muhammad (PRAJA: Jurnal Ilmiah Pemerintahan, 2024)
Optimizing regional tax revenues and regional levies needs to be carried out through intensification and extensification strategies to fund the implementation of regional development. This research aims to; 1) analyze the regional government's strategy in increasing regional tax revenues and regional levies in Sidenreng Rappang Regency, 2) analyze supporting and inhibiting factors in efforts to optimize regional tax and regional levy revenues. This research uses a qualitative approach, the type of research is descriptive. The research informants were Regional Revenue Agency (Bapenda) officials, selected using purposive sampling techniques. The data collection method uses interview and documentation techniques while the data analysis technique uses qualitative data analysis software (QDAS) Nvivo 12. The results of this research show; 1) intensification and extensification strategies in optimizing regional tax and levy revenues in Sidenreng Rappang district have not been maximized. This can be seen from the realization of regional tax and levy revenues which did not reach the target and even experienced a sharp decline from the previous year. 2) Supporting factors for optimizing regional tax and levy revenues include; The legal basis in the form of Regional Regulations and other related regulations is available, PAD is managed centrally by Bapenda, human resources from natural and economic resources, implementation of the QRIS application online payment system. Inhibiting factors include; the level of awareness of some taxpayers is low, the skills of tax officers in the IT sector are still lacking, sanctions are less strict, supervision is weak, and there are minimal incentives for tax officers.